PENDIDIKAN KESEHATAN KEGAWATDARURATAN PENYAKIT KRONIS PADA MASYARAKAT DESA TIBUBENENG - Ni Made Diah Pusparini Pendet; Komang Agus Jerry W; Putu Intan Daryaswanti (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2021)
Background: Adequate level knowledge is necessary in providing proper first aid on chronic disease emergency. This community service aimed to improve the level of knowledge on chronic disease emergency management in Tibubeneng Village, North Kuta, Badung-Bali. Method: An-online-ninety-minutes-health education session was delivered to 22 participants using a PowerPoint and video media. Wilcoxon statistical analysis applied to know the mean difference of the knowledge level before and after the health education session. Result: Finding indicated no significant effect of health education of knowledge level improvement on chronic disease emergency management (p=0.78). Recommendation: We suggest conducting routine health education and interactive sessions such as simulation to enhance the knowledge on chronic emergency disease management.